Decentralizacja władzy publicznej w Polsce na przykładzie samorządu terytorialnego - Antkowiak, Paweł (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
The political and social transformations of 1989 in Poland were primarily related to the profound democratization of the apparatus of public authority, resulting in the almost total abandonment of the unified, centralized structure. In the realm of public administration this process is illustrated by the thorough decentralization of the administrative apparatus. The current model of administration assumes that is it is exercised both by the apparatus of the centralized governmental administration and by a diversified system of independent organs and institutions that perform public tasks vested in them by virtue of law in their own names and on their own accounts. The subject of this paper is the reinstatement of territorial self-government which constituted an integral part of this process.